P‐5.6: Efficient Aging Compensation of AMOLED Displays Based on Data Counting Model. (26th August 2021) - Tang, Rui; Zhang, Tianyou; Tian, Fan; Xu, Jing; Hwang, Jason
Abstract : The fast aging speed has been one of the biggest disadvantages of AMOLED displays, which can cause multiple problems, such as the short lifetime and image sticking phenomenon. The aging compensation based on data counting model is considered as a cost‐effective solution for practical products. However, the compensation for high‐resolution displays at a real‐time speed remains challenging due to the difficulty of processing the huge amount of data. Here, we propose an efficient aging compensation method that can significantly reduce the data amount. Numerical analysis shows that the proposed method is promising for practical use.